Early Grade Teachers’ Professional Competence in Applying Sets to Numbers - Tyas Herwinda; Gunarhadi Gunarhadi; Sri Yamtinah (Social, Humanities, and Educational Studies (SHES): Conference Series, 2024)
This study describes the professional competence of early grade teachers in applying set material in learning number material. The main objective of this study is to describe the competence of early grade teachers on set material applied in learning numbers. This type of research is descriptive qualitative with data collection methods through tests and teaching observations. The results showed that: 21 out of 25 teachers (84%) understood the notion of A∪B but were unable to apply it in addition operation; 24 out of 25 teachers (96%) understood about Cardinal numbers but what was spoken was number not lot; 25 out of 25 teachers (100%) understood the notion of A-B but were unable to apply the notion of subtraction operation.